Initial Encounters: Seeking traces of ancient trade connections between West Africa and the wider world - Sonja Magnavita (Afriques)
The long-standing, more mythical than fact-based assumptions about ancient trade contacts between West Africa and the wider world prior to the Arab conquest of North Africa have only been substantiated by archaeological evidence in recent years. Although the number of imported items known to have been brought into West Africa during late Roman and Byzantine times just started growing, the mechanisms of their diffusion are still far from being understood. This can mainly be set down to the dearth of convincing material evidence from other archaeological sites in West Africa, the Sahara and North Africa — the result of a lack of research and, perhaps too, of trade in “invisible” merchandise Previous archeological studies on this topic are discussed; and the preliminary findings of recent research in the eastern Niger Bend, presented.